Sealing glass for ferrite-dielectric ceramic heterogeneous integration and preparation method thereof

Through the crystallization design and heat treatment of components such as SiO2-ZnO-Li2O-Al2O3-K2O-P2O5-La2O3, the sealing glass in ferrite-die ceramic heterogeneous integration was optimized, and the thermal expansion matching and high-temperature sealing problems were solved. , realizes high thermal, mechanical, electrical properties and narrow welding temperature windows, improving the reliability and welding quality of components.

CN119285234APending Publication Date: 2025-01-10CHENGDU 899 SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411432300.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The sealing glass in the existing ferrite-die ceramic heterogeneous integration is difficult to achieve thermal expansion matching, high-temperature sealing and narrow welding temperature windows, resulting in poor reliability and welding quality of components at high temperatures.

Method used

Seal glass with components such as SiO2-ZnO-Li2O-Al2O3-K2O-P2O5-La2O3-Sm2O3 is optimized through crystallization design and heat treatment control to form the Li2ZnSiO4 isomorphic crystallization phase to achieve Good interface and high thermal, mechanical and electrical properties of ceramic-glass-feltite.

Benefits of technology

The thermal expansion matching of ferrite-die ceramics is achieved, the temperature resistance and welding temperature window of glass are improved, the reliability and welding quality of components at high temperatures are ensured, and the good electrical performance and cost-effectiveness are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285234A_ABST
    Figure CN119285234A_ABST
Patent Text Reader

Abstract

The invention discloses sealing glass for ferrite-dielectric ceramic heterogeneous integration and a preparation method of the sealing glass, and belongs to the technical field of electronic sealing materials. The sealing glass comprises SiO2 (silicon dioxide), ZnO (zinc oxide), Li2O (lithium oxide), Al2O3 (aluminum oxide), K2O (potassium oxide), P2O5 (phosphorus pentoxide), La2O3 (lanthanum oxide), Ce2O3 (cerium The preparation method comprises the following steps: carrying out ball milling on the components by taking alcohol and zirconium balls as media, and drying after ball milling to obtain dry powder; and melting the dried powder into molten glass, and sequentially quenching and drying to obtain the sealing glass. The sealing glass for ferrite-dielectric ceramic heterogeneous integration provided by the invention effectively solves the technical problems that glass in the prior art is difficult to meet the requirements of high thermal expansion coefficient, high-temperature sealing, narrow welding temperature window and the like; when the method is applied to the ferrite-dielectric ceramic heterogeneous integrated welding process, the welding interface can be clear, and the welding quality can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic sealing materials, and in particular relates to a sealing glass for ferrite-dielectric ceramic heterogeneous integration and a preparation method thereof. Background Art

[0002] In the fields of electronic vacuum, electronic component manufacturing, semiconductor packaging, etc., glass is widely used to achieve airtight packaging and integrated connection between ceramics, metals, semiconductors and other materials, in order to obtain good packaging airtightness, connection strength, heat resistance, electrical insulation and other properties.

[0003] The thermal expansion coefficient is one of the important indicators of sealing glass. Achieving thermal expansion matching between glass and sealing components can reduce thermal stress generation, thereby enhancing the reliability of components and products when subjected to temperature shock. In addition, according to the needs of the sealing component manufacturing process and application scenarios, the temperature characteristics of the sealing glass (glass transition temperature T g , softening temperature T f , crystallization temperature T x etc.), mechanical and electrical strength, thermal and chemical stability are also important indicators.

[0004] In the ferrite-dielectric ceramic heterogeneous integration process, the glass needs to have good wettability to both ferrite and ceramic to ensure a good welding interface. The sealing temperature is usually expected to be no higher than 1200°C to protect the ferrite material used, which requires the glass to have a certain fluidity at the sealing temperature, that is, T f In addition, considering the silver coating process of heterogeneous integration, the glass needs to be compatible with the silver paste and withstand 800-950℃, that is, T f It is higher than the co-firing temperature, which makes the welding temperature window relatively narrow.

[0005] The thermal expansion coefficient of ferrite and dielectric ceramic materials is generally 8-11ppm / ℃ (room temperature-400℃). Considering only the thermal expansion coefficient, most sealing glasses can achieve thermal expansion matching. However, most sealing glasses cannot meet the requirements of the high sealing temperature and narrow sealing temperature window of the above-mentioned integration process.

[0006] For example, the lead-free sealing glass system (thermal expansion coefficient greater than 8ppm / ℃) mainly includes SiO2-B2O3-based, SiO2-Al2O3-RO (R = alkaline earth metal element)-based, P2O5-ZnO-based, Bi2O3-B2O3-ZnO, etc. For example, Chinese invention patent CN106495490 discloses a Bi2O3-B2O3-ZnO-SiO2 sealing glass, whose thermal expansion coefficient can reach 12-13ppm / ℃, but it is only suitable for low-temperature sealing below 500℃. Chinese invention patent CN109250916 discloses a SiO2-B2O3-based sealing glass, which has a thermal expansion coefficient of 9-10ppm / ℃, but the welding temperature is 850-1000℃, and the temperature resistance is still not high enough. Chinese invention patent CN102060440 discloses a SiO2-Li2O-based sealed microcrystalline glass, which can achieve a thermal expansion coefficient of 10-11 ppm / °C after heat treatment and has a relatively high sealing temperature of 1000-1050°C. However, its temperature resistance window remains to be clarified.

[0007] Li2O-ZnO-SiO2 glass-ceramics are a type of sealing system with a high welding temperature (usually greater than 1000°C) and a high thermal expansion coefficient (higher than 10ppm / °C after crystallization). For example, Chinese invention patent CN104529164 discloses a Li2O-ZnO-SiO2 sealing glass, which obtains a high thermal expansion coefficient of 13-19ppm / °C after heat treatment at 600-800°C, but its crystallization phase includes multiple phases such as lithium disilicate, quartz, and zinc silicate, which will bring about complex welding behavior and is not conducive to obtaining a good welding interface. Chinese invention patent CN113461337 discloses a Li2O-ZnO-SiO2 glass-ceramics with a welding temperature of 1020-1070°C, but its crystallization phase and glass temperature characteristics are not described, so it is impossible to judge its thermal shock resistance, temperature-resistant window, and silver co-firing behavior.

[0008] In view of the above research status and technical application requirements, it is extremely important to provide a packaging glass suitable for ferrite-dielectric ceramic heterogeneous integration. Summary of the invention

[0009] Based on this, the present invention aims to provide a sealing glass for ferrite-dielectric ceramic heterogeneous integration and a preparation method thereof. The sealing glass can achieve thermal expansion matching with ferrite-dielectric ceramic and has good temperature resistance (T f >900℃), narrow soldering temperature window (T f <1050℃), good thermal shock resistance, good electrical properties, etc.

[0010] The object of the present invention is achieved through the following technical solutions:

[0011] A sealing glass for ferrite-dielectric ceramic heterogeneous integration, comprising the following components in parts by weight:

[0012] 50-69 parts SiO2, 20-35 parts ZnO, 8-12 parts Li2O, 0-5 parts Al2O3, 2-4 parts K2O, 2-4 parts P2O5, 0-2wt parts La2O3, 0-2 parts Ce2O3 and 0-2 parts Sm2O3.

[0013] The functions of the components of the sealing glass of the present invention are as follows:

[0014] SiO2 is the main component of the glass network; Li2O and ZnO participate in crystallization on the one hand, and can reduce the glass melting temperature and adjust the glass T g The temperature characteristics and thermal expansion coefficient of the glass are the same, especially Li2O can play the role of a strong flux; P2O5 is a nucleating agent, which can become a nucleation point in the glass network, promote the precipitation of tiny grains of the target phase, and then improve the sealing strength, thermal shock resistance and chemical stability of the glass; if the P2O5 content is too much (>6%), it will bring about a phase separation effect, which is not conducive to the realization of a single crystallization phase. The addition of an appropriate amount of K2O is used to assist Li2O in adjusting the temperature characteristics and thermal expansion coefficient of the glass (K2O is more efficient in improving thermal expansion than Li2O); in addition, K2O enters the gap of the glass network, which can effectively improve the chemical stability and strength of the glass at the nucleation temperature; Al2O3 is a glass intermediate, and its role in the glass network will strongly depend on the components of the glass. The appropriate amount of addition can improve the stability of the glass and adjust the thermal expansion coefficient and temperature resistance of the glass; Ln series elements (La, Ce, Sm) are used to modify the glass network, and in the present invention, they play the role of adjusting the melting temperature and thermal expansion coefficient, while improving the stability of the glass and improving the airtightness.

[0015] The thermal expansion coefficient of Li2ZnSiO4 ceramic phase is generally around 11ppm / ℃. The present invention is designed around the crystallization of single-phase Li2ZnSiO4, thereby achieving control of the thermal expansion coefficient and obtaining good welding behavior and welding interface. Adjusting the ratio of Li2O-ZnO-SiO2 is the main means of regulation. Theoretically, when the molar ratio of Li2O / ZnO is 1, Li2ZnSiO4 phase will be precipitated first. At the same time, depending on the content of SiO2, the crystallization phase may be SiO2, Li3Zn 0.5 The present invention determines that the optimal SiO2 content is 50-69wt%, and the glass has suitable temperature characteristics; on this basis, Li2O is added, and the main crystallization phase is transformed into Li2Si2O5, Li2SiO3 and SiO2, etc.; if the ZnO content is increased, the main crystallization phase is Zn2SiO4 and SiO2, etc.

[0016] The present invention realizes the precipitation of Li2ZnSiO4 target phase and effectively controls the thermal expansion coefficient through reasonable crystallization component design and heat treatment temperature control. The control of the crystal phase type not only obtains the appropriate thermal expansion coefficient, realizes the good interface of ceramic-glass and glass-ferrite, reduces the generation of cracks, and improves the workpiece quality. In addition, the use of crystallization means can cause the softening of glass to increase, greatly improve the temperature resistance of glass, thereby meeting the silvering process; the crystallization means also improves the thermal, mechanical and electrical qualities of glass. The regulation of glass components and additives allows it to experience the glass deformation point, expansion softening point, and glass softening point at 900-1000°C, and the softening point and glass flow point temperature at 1000-1100°C, realizing a narrower welding temperature window for glass.

[0017] The sealing glass prepared by the present invention matches the thermal expansion of the ferrite-dielectric ceramic and has good temperature resistance (T f >900℃), narrow soldering temperature window (T f <1050℃), good heat shock resistance and good electrical properties, which effectively solves the technical problems of sealing glass in the existing technology that are difficult to meet high thermal expansion coefficient, high temperature sealing, narrow welding temperature window, etc.

[0018] In addition, the raw materials of the sealing glass described in the present invention do not use volatile components such as B2O3 and As2O3, which effectively avoids the ratio deviation caused by volatilization during the glass preparation process, improves the formula reproducibility and powder batch stability; the raw materials also do not use some expensive components such as gallium oxide and tellurium oxide, and the cost is relatively low.

[0019] As an embodiment of the present application, the transition temperature of the sealing glass is 420-480°C, the first crystallization temperature range is 600-750°C, the second crystallization temperature range is 800-900°C, and the softening temperature is 920-1010°C.

[0020] As an implementation manner of the present application, the thermal expansion coefficient of the sealing glass is 7-10 ppm / °C. After heat treatment at 900°C, the thermal expansion coefficient is 11-15 ppm / °C.

[0021] As an embodiment of the present application, the insulation resistance of the sealing glass is 4×10 12 -8×10 12 Ω·cm, and the breakdown voltage is 10-14kV / mm.

[0022] In addition, to achieve the above-mentioned purpose, the present invention also provides a method for preparing sealing glass for ferrite-dielectric ceramic heterogeneous integration, comprising the following steps:

[0023] S1 Take SiO2, ZnO, Li2O, Al2O3, K2O, P2O5, La2O3, Ce2O3 and Sm2O3, use alcohol and zirconium balls as media for ball milling, dry after ball milling to obtain dry powder;

[0024] S2: melting the dry powder into glass liquid, and then quenching and drying the liquid to obtain sealing glass.

[0025] The glass liquid can be added into a mold to be prepared into a column or plate shape, or further broken into glass powder.

[0026] As an implementation mode of the present application, in the melting process of step S2, the temperature is 1450-1550°C.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention realizes the precipitation of Li2ZnSiO4 target phase and effectively controls the thermal expansion coefficient through reasonable crystallization component design and heat treatment temperature control. The control of crystal phase types not only obtains a suitable thermal expansion coefficient, realizes a good interface between ceramics-glass and glass-ferrite, reduces the generation of cracks, and has high workpiece quality. In addition, the use of crystallization means can cause the softening of glass to increase, greatly improve the temperature resistance of glass, thereby meeting the silvering process; the crystallization means also improves the thermal, mechanical and electrical qualities of glass. The regulation of glass components and additives allows it to experience the glass deformation point, expansion softening point, and glass softening point at 900-1000°C, and the softening point and glass flow point temperature at 1000-1100°C, achieving a narrower welding temperature window for glass, effectively solving the technical problems in the prior art that it is difficult for glass to meet high thermal expansion coefficients, high-temperature sealing, and narrow welding temperature windows.

[0029] Specifically, the sealing glass in the present invention has the following characteristics:

[0030] ①Conversion temperature (T g ) is 420-480℃, the first crystallization temperature (T x ) range is 600-750℃, the second crystallization temperature (T x ) range is 800-900℃, softening temperature (T f ) at 920-1010°C;

[0031] ②The thermal expansion coefficient is 7-10ppm / ℃, and after heat treatment at 900℃, it is 11-15ppm / ℃;

[0032] ③Insulation resistance is 4×10 12 -8×10 12 Ω·cm, and the breakdown voltage is 10-14kV / mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 : DSC-TG graph of the sealing glass in Example 1;

[0034] Figure 2 : XRD of the sealing glass sintered at different temperatures in Example 1;

[0035] Figure 3 : Test diagram of thermal expansion coefficient of sealing glass in Examples 1-3;

[0036] Figure 4 : Actual welding workpiece and welding interface diagram. DETAILED DESCRIPTION

[0037] Example 1

[0038] S1 weighed 59.2 parts of SiO2, 25 parts of ZnO, 9 parts of Li2O, 2 parts of Al2O3, 2 parts of K2O and 2.8 parts of P2O5, then these raw materials were ball-milled with alcohol and zirconium balls as the medium for 3 hours, and then put into an oven and dried at a temperature of 130°C to obtain dry powder;

[0039] S2: placing the dried powder in a furnace, first heating it to 1400°C at a heating rate of 8°C / min, keeping it warm for 1 hour, then heating it to 1500°C at a heating rate of 5°C / min, keeping it warm for 0.5 hour, then pouring pure water into it for quenching, further crushing it into glass powder, and drying it.

[0040] The sealing glass in Example 1 was subjected to DSC-TG test. Figure 1 ,Depend on Figure 1 It can be seen that the T of the sealing glass g 456℃, T f is 1004°C, and the peak crystallization temperature of the glass is T m 708℃ and 880℃.

[0041] The sealing glass in Example 1 was further heat treated at 400°C, 700°C, 900°C, and 1000°C for 1 h, and XRD test was performed. Figure 2 .

[0042] Depend on Figure 2It can be seen that the glass without heat treatment and heat treatment at 400℃ presents an amorphous peak package; when the heat treatment temperature is higher than 700℃, the target phase Li2ZnSiO4 appears, and the diffraction peak intensity of the target phase increases under heat treatment at 900-1000℃, indicating that its content and crystallinity are improved. At the same time, a small amount of impurity phase will appear, such as the more obvious phosphorus quartz at 1000℃. The XRD heat treatment at 1100℃ shows the melting state of the crystalline phase. The XRD results prove that the regulation of the crystallization phase in the embodiment is very successful.

[0043] Example 2

[0044] S1 weighed 58 parts of SiO2, 25 parts of ZnO, 9 parts of Li2O, 2 parts of Al2O3, 2 parts of K2O, 3 parts of P2O5, 0.5 parts of La2O3 and 0.5 parts of Ce2O3, then these raw materials were ball-milled with alcohol and zirconium balls as the medium for 3 hours, and then put into an oven and dried at a temperature of 130°C to obtain dry powder;

[0045] S2: placing the dried powder in a furnace, first heating it to 1400°C at a heating rate of 8°C / min, keeping it warm for 1 hour, then heating it to 1500°C at a heating rate of 5°C / min, keeping it warm for 0.5 hour, then pouring pure water into it for quenching, further crushing it into glass powder, and drying it.

[0046] Example 3

[0047] S1 weighed 57 parts of SiO2, 24 parts of ZnO, 9 parts of Li2O, 2 parts of Al2O3, 4 parts of K2O, 3 parts of P2O5, 0.5 parts of La2O3 and 0.5 parts of Ce2O3; then these raw materials were ball-milled with alcohol and zirconium balls as the medium for 3 hours, and then placed in an oven and dried at a temperature of 130°C to obtain dry powder;

[0048] S2: placing the dried powder in a furnace, first heating it to 1400°C at a heating rate of 8°C / min, keeping it warm for 1 hour, then heating it to 1500°C at a heating rate of 5°C / min, keeping it warm for 0.5 hour, then pouring pure water into it for quenching, further crushing it into glass powder, and drying it.

[0049] The thermal expansion coefficients of the sealing glasses in Examples 1-3 and the sealing glass in Example 1 after heat treatment at 900°C were tested respectively. Figure 3 and Table 1.

[0050] The electrical properties of the sealing glasses in Examples 1-3 were tested, see Table 1.

[0051] Through Table 1 and Figure 3It can be seen that by adjusting the composition of the glass, the thermal expansion coefficient of the sealing glass can be adjusted to have a good thermal expansion coefficient and good electrical properties. In Example 1, after heat treatment at 900°C, the thermal expansion coefficient is increased to 14 ppm / °C.

[0052] Table 1

[0053]

[0054] Example 4

[0055] The sealing glass in Example 1 is coated between the ferrite and the dielectric ceramic, heated to 1050-1200°C in a box furnace at a rate of 3-8°C / min and with good adaptability to ferrite-dielectric ceramic heterogeneous integration, welded for 1-2h, cooled to room temperature at 3-5°C / min, silvered at 850-900°C, and kept at this temperature for 0.5-1h to obtain the workpiece.

[0056] The welding condition was analyzed by optical microscope (such as Figure 4 The left figure) and the use of electron microscopy to analyze the microscopic welding interface (such as Figure 4 (right image).

[0057] Depend on Figure 4 It can be seen that from the optical microscope, the ferrite-dielectric ceramic workpiece is intact; from the electron microscope, the welding interface is clear and the welding quality is good.

[0058] It is worth noting that the present invention uses a thermal analysis instrument DSC-TG to test the sealing glass, including analyzing the glass transition temperature T g , softening temperature T f , crystallization peak temperature T m Isothermal characteristics;

[0059] Use a thermal expansion analyzer to test the thermal expansion coefficient of the sealing glass;

[0060] An impedance meter and a high voltage source fixture are used to test the electrical properties of the sealing glass, such as resistance and breakdown voltage.

Claims

1. A sealing glass for ferrite-dielectric ceramic heterogeneous integration, characterized in that: It includes the following components by weight: 50-69 parts SiO2, 20-35 parts ZnO, 8-12 parts Li2O, 0-5 parts Al2O3, 2-4 parts K2O, 2-4 parts P2O5, 0-2 parts La2O3, 0-2 parts Ce2O3 and 0-2 parts Sm2O3.

2. The sealing glass for ferrite-dielectric ceramic heterogeneous integration according to claim 1, characterized in that: The conversion temperature is 420-480°C, the first crystallization temperature range is 600-750°C, the second crystallization temperature range is 800-900°C, and the softening temperature is 920-1010°C.

3. The sealing glass for ferrite-dielectric ceramic heterogeneous integration according to claim 1, characterized in that: The thermal expansion coefficient is 7-10ppm / ℃. After heat treatment at 900℃, the thermal expansion coefficient is 11-15ppm / ℃.

4. The sealing glass for ferrite-dielectric ceramic heterogeneous integration according to claim 1, characterized in that: Insulation resistance is 4×10 12 -8×10 12 Ω·cm, and the breakdown voltage is 10-14kV / mm.

5. The method for preparing sealing glass for ferrite-dielectric ceramic heterogeneous integration according to claim 1, characterized in that: The steps include: S1 Take SiO2, ZnO, Li2O, Al2O3, K2O, P2O5, La2O3, Ce2O3 and Sm2O3, use alcohol and zirconium balls as media for ball milling, dry after ball milling to obtain dry powder; S2: melting the dry powder into glass liquid, and then quenching and drying the liquid in sequence to obtain sealing glass.

6. The method for preparing sealing glass for ferrite-dielectric ceramic heterogeneous integration according to claim 5, characterized in that: In the melting process of step S2, the temperature is 1450-1550°C.